Two-dimensional resonators for local oscillators - Huang, K; Jenkins, A; Edwards, D; Dew-Hughes, D (IOP, 1999)
The expedited globalization of satellite technology has brought about a rapid boost in satellite competition and increased utilization of wireless communications remote data devices. In space communications receivers, there is an expanding demand for higher performance from local oscillators. The determining conditions are high Q values, high circulating power and low amplifier noise figures. In spite of their low insertion loss, conventional one-dimensional high-temperature superconducting (HTS) resonator-feedback oscillators suffer from high peak current densities inside the resonator and thus have a limited power-handling characteristics. To achieve higher-power oscillators, it is possible to introduce a two-dimensional microstrip resonator to balance the internal current distribution. To this end, 3 GHz two-dimensional resonators have been fabricated from TBCCO 2212 thin films deposited by RF sputtering onto 2 cm square LaAlO3 substrates. This paper demonstrates the frequency stabilizer role and the frequency response of the two-dimensional resonator. The considerable improvement for the performance of resonator-feedback oscillators constructed using such HTS resonators will also be presented.